Chemical and bromatological evaluation of varieties Yurac llajum, Qello llajum y Yurac checche of Smallanthus sonchifolius (Poepp & Endl) H. Robinson (yacón) from Puno - Ramos Zapana, Rubén (2010)
The varieties Yurac llajum, Qello llajum y Yurac Checche of the species Smallanthus sonchifolius (Poepp & Endl) (Yacón), coming from the province of Sandia, Department of Puno, it is developed from 1500 to 3000 msnm, also are well-known like “yacón”, “yakuma”, “llaqón”, “ llacun” and “llacuma” in quechua language; “aricoma” and “aricuma“ in aymara language; “Yacón”, “Jacón”, “llacón”, “arboloco”, “Puhe”, “jicama”, “jíquima”, “jikima” y “jiquimilla” in Spanish. These tuberose roots of sweet and refrescante (refreshing?) flavor, of granulate aspect, white yellowish and forms extended show an average of: weight of 248,70 g by plant, a length of 17,16 cm, 15 roots by plant, and 6,20 cm of diameter of root by plant. It presents a content of water of 80,83 to 87,05; total protein 2,76 to 2,86; ash 2,78 to 2,92; etéreo extract 0,27 to 0,29; crude fiber 4,07 to 4,34; carbohydrates 89,53 to 90,86; sugar direct reducers 7,04 to 8,14; sugar total reducers 25,33 to 27,65 and total acidity 0,27 a 0,32; all considered in grams percent.